Riesgos físicos y mecánicos procedentes de las actividades laborales de la constructora LEONARDO HERNÁNDEZ S.A., Cantón Esmeraldas - Cedeño García, Gloria Alejandra (2023)
The personnel of a construction company are the most vulnerable to suffer injuries at work due to the inadequate operation of machinery, when carrying out a sudden movement with dangerous materials or objects, so it is essential to identify the physical and mechanical risks to which they are exposed. The objective of this research is to evaluate the relationship between physical and mechanical risks and the work activities carried out by employees of the construction company Leonardo Hernández S.A. in Esmeraldas canton. Information was collected through surveys, interviews and several field visits, and it was possible to identify that the company carries out 5 processes with different work activities. Monitoring was carried out with a luxmeter, vibrometer, sonometer and thermhygrometer for the evaluation of physical risks, while the matrix proposed by the Ministry of Labour was used for mechanical risks. William Fine's methodology and the Matrix of Occupational Risks proposed by the Ministry of Labour were used for estimation and assessment, resulting in workers being exposed to the following risks: (high, medium, low). It was determined that in the operational area there is a greater presence of physical and mechanical risks, with 4 physical risks and 13 mechanical risks in their work activities. Based on the information obtained, an occupational risk prevention plan was drawn up that focuses on improving the working environment of its workers, in order to promote the safety and well-being of the company's personnel.